2012
DOI: 10.1371/journal.pone.0046906
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Depression and Risk of Recurrent Stroke at 1 Year in a Chinese Cohort Study

Abstract: BackgroundStudies show that poststroke depression (PSD) increases mortality risk at 1 year. However, whether PSD increases the risk of recurrent stroke at 1 year remains unclear. This study was to investigate whether PSD at 2 weeks following a stroke could increase risk of recurrent stroke at 1 year.Methods and ResultsThis was a multi-centered prospective cohort study. A total of 2306 patients with acute stroke were enrolled in our study. PSD was diagnosed according to the criteria set by the Diagnostic and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
(31 reference statements)
3
55
2
1
Order By: Relevance
“…These results were consistent with previous studies of depression in older patients with stroke (Cheng et al, 2005;Li et al, 2003). However, previous studies of communitydwelling patients with stroke suggested that being a woman (Liao et al, 2004), being older (Farner et al, 2010), and having a higher risk of stroke recurrence (Yuan et al, 2012) were significantly associated with depression symptoms. More studies are needed to confirm our research findings regarding the relationships between demographic data and depression in older residents of LTCFs with stroke.…”
Section: The Journal Of Nursing Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were consistent with previous studies of depression in older patients with stroke (Cheng et al, 2005;Li et al, 2003). However, previous studies of communitydwelling patients with stroke suggested that being a woman (Liao et al, 2004), being older (Farner et al, 2010), and having a higher risk of stroke recurrence (Yuan et al, 2012) were significantly associated with depression symptoms. More studies are needed to confirm our research findings regarding the relationships between demographic data and depression in older residents of LTCFs with stroke.…”
Section: The Journal Of Nursing Researchsupporting
confidence: 91%
“…Poststroke depression has been associated with brain damage and increased disability, cognitive impairment, and mortality (Robinson, 2003;Whyte & Mulsant, 2002). Previous studies have shown that gender (Liao et al, 2004), age (Farner et al, 2010;Hornsten, Molander, & Gustafson, 2012), and risk of recurrent stroke (Yuan et al, 2012) are factors associated with depressive symptoms in poststroke patients.…”
Section: Resultsmentioning
confidence: 99%
“…PSD significantly influences the patients' cognition, recovery and daily life. It is reported that the morbidity of PSD within two weeks is 28.1% [3,4], within a year is 61%, and within two years is 79% [5,6]. However, benefit of present used antidepressant drug was not satisfactory [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…PSD significantly affects the cognition, recovery and daily life of the stroke patients. It has been reported that the incidence of PSD was 28.1% in 2 weeks after stroke attack, 61% within 1 year, even higher (79%) in 2nd year following the stroke [2, 3]. Nevertheless, the clinical efficacy of the current anti-depression agents is relatively limited [4].…”
Section: Introductionmentioning
confidence: 99%